1983
DOI: 10.1038/bjc.1983.208
|View full text |Cite
|
Sign up to set email alerts
|

The sex hormone profile of male patients with breast cancer

Abstract: Summary The mean total serum oestradiol level was found to be significantly increased in 8 male patients with carcinoma of the breast when compared with 8 healthy reference subjects matched for race, sex and age. The calculated mean free oestradiol index was also higher in these patients. There were no significant differences, however, between the levels of LH, FSH, prolactin, DHEA-S, testosterone and SHGB in the 2 groups. The patients showed a significantly increased LH response to GnRH while there was no dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
3

Year Published

1985
1985
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 11 publications
1
15
0
3
Order By: Relevance
“…However, this suppression was inadequate to produce a therapeutic response. Basal oestradiol levels in our series were in the same range as reported by Nirmul et al (1982). The patients were not intrinsically resistant to endocrine therapy, since 3 out of 4 responded to tamoxifen.…”
Section: Resultssupporting
confidence: 72%
“…However, this suppression was inadequate to produce a therapeutic response. Basal oestradiol levels in our series were in the same range as reported by Nirmul et al (1982). The patients were not intrinsically resistant to endocrine therapy, since 3 out of 4 responded to tamoxifen.…”
Section: Resultssupporting
confidence: 72%
“…In a previous report (Ribeiro, 1977) (1973) but not with other reports (Dao et al, 1973, Calabresi et al, 1976Nirmul et al, 1982). The reasons for the difference may be in the methodology, the paucity of patients, the choice of controls, or even due to ethnic variations.…”
Section: Discussionmentioning
confidence: 96%
“…[3] In Manchester, England, a 0.7 percent inci¬dence was reported, unchanged from the previous report in 1977. [19] Higher rates are reported in blacks, including 2.4 percent among West Africans in the report by Ajayi et al [4] and a three percent incidence in black males by Nirmul et al [5] An unusually high incidence is reported in Zambia, where 15 percent of all breast cancer is in males. [6] In Virginia, there is a disproportionately higher percentage of male breast cancer in black males (24 percent) in comparison with black females (16 percent).…”
Section: Disucssionmentioning
confidence: 92%